The responses of photosynthesis, fruit yield and quality of mini-cucumber to led-interlighting and grafting - De Freitas, Isabela S.; Roldán, Gustavo Q.; Macedo, Ana Claudia [UNESP]; Mello, Simone Da C. (FapUNIFESP (SciELO), 2021)
Supplemental lighting is becoming a common practice for horticultural greenhouse industries, especially at high-latitude countries. However, no scientific reports were found on this topic in tropical climate countries. This study investigates the effects of LED-interlighting and grafting on photosynthetic response and yield and quality of mini cucumber (hybrid Larino). The experiment took place from April to August in a greenhouse located at a Cwa climate type in Piracicaba (SP), Brazil (22°42’S; 47°37’W; 541 m altitude). The experiment was arranged in completely randomized block design composed of three types of seedlings (ungrafted hybrid, hybrid grafted onto rootstock cultivar Keeper and hybrid grafted onto rootstock cultivar Shelper) and two environments related to light condition (LED supplemental light and natural light as control). The LED devices were placed horizontally at 15 cm from the plants and at 1,5 m height from the floor. The LEDs emitted a photon flux of 220 µmol m-2 s-1 by red light (80%) with a peak wavelength of 662 nm and blue light (20%) with a peak wavelength of 452 nm. Lighting was used for 12 h d-1 from 30 days after seedling transplanting until the end of the growth period. The air temperature and relative humidity (RH) were maintained at 23.5±4°C and 72±10% during the light period, respectively. At night, average temperature was 18.6±5°C and the RH was 90±5%. The LED-interlighting treatment increased in 40% the plant CO2 net assimilation rate compared to plants grown under natural light in the greenhouse. Plants grafted onto both rootstocks had higher CO2 net assimilation rate (µmol CO2 m-2 s-1), apparent carboxylation efficiency (µmol CO2 mol air-1) and apparent electron transport rate (µmol electrons m-2 s-1) than non-grafted ones. The early yield increased 11.6% and 24% in response to LED-interlighting and grafting, respectively. The commercial yield also increased with LED light at rate of 13% but did not enhance with grafting. Postharvest quality parameters as titratable acidity, total soluble solids and shelf life were not affected by the LED light supplementation. Our study shows that even in tropical climate conditions LED-interlighting can be used as a tool to improve commercial cucumber production.
Respostas da fotossíntese, produtividade e qualidade de mini pepino à iluminação com barras de LED no interior do dossel e à enxertia
Keywords: CO2 rate; Cucumis sativus; Grafting; Postharvest; Supplemental lighting